A Detailed Theoretical Study of Cu3Agm Bimetallic Clusters - Leite, Francinaldo dos Santos (2021)
In this work, we explored the energy landscape and the effect of increasing the amount of Ag atoms over the segregation of Cu atoms in bimetallic clusters with compositions Cu3Agm (), using a genetic algorithm coupled with the Gupta potential to determine the most stable clusters. According to our results, the Ag atoms determine the magic compositions, which are the Cu3Ag10, Cu3Ag16 and Cu3Ag20 clusters. In all studied structures, the Cu atom establishes an interface with the Ag atoms or tends to form a core-shell structure with at least one Cu atom on the cluster surface. Scalar relativistic DFT calculations of the magic compositions reveal that these clusters have an electronic behavior similar to their pure Ag analogues. DOI: http://dx.doi.org/10.17807/orbital.v13i3.1536